2017
DOI: 10.4269/ajtmh.16-0399
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Scrub Typhus, Typhus, and Spotted Fever Among Rural and Urban Populations of Northern Vietnam

Abstract: Rickettsial infections are recognized as important causes of fever throughout southeast Asia. Herein, we determined the seroprevalence to rickettsioses within rural and urban populations of northern Vietnam. Prevalence of individuals with evidence of prior rickettsial infections (IgG positive) was surprisingly low, with 9.14% (83/908) testing positive to the three major rickettsial serogroups thought to circulate in the region. Prevalence of typhus group rickettsiae (TG)–specific antibodies (6.5%, 58/908) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 20 publications
1
19
3
1
Order By: Relevance
“…The reported seroprevalence of O . tsutsugamushi for each country is shown in Table 1 [ 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ]. The reports of outbreaks of scrub typhus are summarized in Table 2 [ 43 , 94 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported seroprevalence of O . tsutsugamushi for each country is shown in Table 1 [ 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ]. The reports of outbreaks of scrub typhus are summarized in Table 2 [ 43 , 94 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , …”
Section: Methodsmentioning
confidence: 99%
“…There was only one study in the central part of Vietnam, Quang Nam province, which identified that the main genotype in the area was the Karp group [ 180 ]. Recent studies of scrub typhus in North Vietnam demonstrated that the cumulative incidence of scrub typhus was about 1.1% among the general population, and ~3.5% among patients admitted to hospitals [ 103 , 105 ]. The peak season in North Vietnam is summer though cases occur throughout the year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1915, a fever of unknown etiology among two individuals was reported in Saigon, Vietnam [ 50 ] to be a disease similar to that described in Deli, Sumatra (i.e., pseudotyphoid), that was later determined to be scrub typhus [ 24 ]. Subsequently, the presence of scrub typhus throughout Vietnam was confirmed [ 38 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Early History Of Scrub Typhus and The Etiologic Agents Ofmentioning
confidence: 99%
“…In Vietnam, the serum antibody prevalence of Orientia tsutsugamushi causing scrub typhus, Rickettsiatyphi causing murine typhus and other Rickettsia of spotted fever group in the community of northern Vietnam were 1.7%; 6.5% and 1.1%, respectively. 7 There have been reports of R. felis causing human illness in central Vietnam. 8 In the National Hospital for Tropical Diseases, Rickettsioses account for one-third of acute undifferentiated fevers with the mortality rate of 5.4% between 2015 and 2017.…”
Section: Introductionmentioning
confidence: 99%